2017
DOI: 10.1177/2325957417711255
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus–Associated Lips Verrucous Carcinoma in HIV-Infected Male

Abstract: Human papillomavirus (HPV) infection, widely known as the necessary cause of cervical cancer, has been established as a major etiologic factor for head and neck cancer (HNC). HIV-infected individuals are at higher risk of HPV-associated cancers than the general population. We describe a 45-year-old man with HIV and HPV coinfection, who presented progressively enlarging verrucous neoformations of the lips. The final diagnosis of verrucous carcinoma was delayed. Early detection of HPV lesions in oral mucosa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Thus, the number of HPV + HNC cases are increasing in HIV/AIDS population compared to non-HPV + HNC cases (in the same population). It is worth mentioning that in some HIV patients, HPV + HNC (especially HPV + OSCCs) have been reported concurrently with HPV-associated anal cancers [61,62], especially in men who have sex with men. Overall, the number of HPV + HNC cases (i.e., in HIV/AIDS and non-HIV/AIDS populations) are higher in men compared to women [59,63,64].…”
Section: Influence Of Immunosuppression In Hpv + Hncmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the number of HPV + HNC cases are increasing in HIV/AIDS population compared to non-HPV + HNC cases (in the same population). It is worth mentioning that in some HIV patients, HPV + HNC (especially HPV + OSCCs) have been reported concurrently with HPV-associated anal cancers [61,62], especially in men who have sex with men. Overall, the number of HPV + HNC cases (i.e., in HIV/AIDS and non-HIV/AIDS populations) are higher in men compared to women [59,63,64].…”
Section: Influence Of Immunosuppression In Hpv + Hncmentioning
confidence: 99%
“…While most patients with HIV/HPV co-infections on HAART therapy have a reduced risk of developing HPV-associated cancer (cervical cancer) compared to patients on non-HAART therapy (reviewed in ref. [93]), some HIV/HPV patients on HAART therapy seem to have a high risk of developing HPV-associated oral lesions/cancers [62,94,95]; the risk is suggested to be due to longer life expectancy as a result of HAART therapy. It is unclear why HAART therapy may have different indirect effects on HPV + HNC versus HPV-associated cervical cancers.…”
Section: Challenges Associated With Hpv + Hncmentioning
confidence: 99%
“…Developing the cancerous lesion after HPV infection may be associated with the immune status of the patients. De Socio et al has reported a case of HPVassociated lips verrucous carcinoma in HIV-infected male patient [13]. HIV-positive patients have a 2 to 3 times higher prevalence of oral HPV infection than HIVnegative patients.…”
Section: Association Between Vce and Human Papilloma Virus Infectionmentioning
confidence: 99%